Construction waste management practices in Malaysia: an overview - Hissham, Nur Fatin Nabila; Abdul Kadir, Aeslina; Toh, Wee Fern; Sarani, Noor Amira; Hassan, Mohd Ikhmal Haqeem; Abdul Hamid, Nur Jannah; Hashar, Nurul Nabila Huda; Hashim, Azini Amiza (Penerbit UTHM, 2020)
The construction industry is one of the major wealth-generating industries and is seen as an elevated sector in the Malaysia economy. However, this activity has generated a significant amount of waste which is detrimental to the environment. The increasing amount of waste from construction projects has shown that construction waste management has not been practised effectively in Malaysia. Therefore, an overview of the composition of construction waste and existing waste management practices on construction sites in Malaysia are the highlights of this study. The findings can potentially be used to enhance the effectiveness of construction waste management in Malaysia and create awareness among contractors for a better alternative in managing the construction waste on-site. Current practices in the construction sector need to be analysed in order to enhance strategies so that improved and more sustainable design, development, operation and maintenance will be attained, leading to minimal waste.